Rancang Bangun Desain dan Evaluasi Robot Cleaner Solar Photovoltaics Menggunakan Komunikasi Nirkabel Berbasis Komunikasi Radio Frekuensi : Robot Cleaner Solar Photovoltaics - Nugroho, Oktavianus Ardhian; Y. B. Adyapaka Apatya (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
The development of robotics technology today has developed rapidly. Many types of work that are done can be done with robots, especially if the work has a high level of accuracy. One of the jobs that require a high level of precision and accuracy is the work of cleaning the solar cell module. To get the maximum and continuous energy level from the sun, the cleanliness level of the solar cell module must always be maintained. Partial shading such as muddy and dusty results in a reduced level of electrical power generated. That's why it's important to keep solar panels clean. In this study, a solar cell module cleaning robot has been designed and tested directly in the field. The purpose of designing this robot is to ensure the cleanliness of the solar cell module from partial shading. The design created using two left-right drive motors is equipped with a brush motor for the cleaning system. Another addition is that this robot is controlled with a Wireless control system based on radio frequency (RF) communication and is equipped with sensors to determine the water level, as well as sensors that can keep the movement of the solar cleaner robot above the solar cell module when working.